(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the fast-paced realm of the IT sector, achieving an optimal work-life balance is not merely a personal pursuit but emerges as a critical catalyst for enhancing productivity, job satisfaction, and overall well-being among employees.Through this paper the reasesrcher tries to explores the pivotal role of work-life balance in optimizing the performance of employees, shedding light on the multifaceted interplay between professional demands and personal well-being.The purpose of this study was to look into the factors that influence work-life balance, employee productivity, working hours, high levels of stress, and burnout among IT industry employees in the Ernakulam district. Employees who worked more hours than a typical full-time workweek and were stressed out were less productive. A strong positive relationship between work-life balance and employee performance was discovered in this study. Employee productivity increased as work-life balance improved. These findings emphasize the significance of a healthy work-life balance in improving overall productivity and well-being. According to the study, long working hours, high stress, and burnout are identified as significant factors affecting the work-life balance of IT industry workers in Ernakulam. These issues can cause employees to feel overwhelmed, exhausted, and unable to maintain a healthy work-life balance. Organizations and policymakers are encouraged to implement work time management and stress reduction strategies to create a positive working environment that improves employee performance. It should be noted that this study finds a strong relationship between work-life balance and employee performance. However, more research is required to investigate the causal relationship between these variables and to quantify other factors influencing work-life balance and employee productivity in the Ernakulam IT sector.